Horseshoe bats foraging in the wild adjust sensing to separate prey echoes from background clutter - Yossi Yovel; Laura Stidsholt; Yotam Mimran; Mor Taub; Stefan Greif; Antoniya Hubancheva; Ivailo Borissov; Anthony J. Weiss; Annette Denzinger; Hans-Ulrich Schnitzler (Proceedings of the National Academy of Sciences, 2026)
How animals handle immense incoming sensory information and regulate sensing is difficult to study under natural conditions. Using miniature GPS tags with microphones we monitored the sensing of freely foraging greater horseshoe bats. Bats stayed in acoustic contact with the environment and caught insects while commuting and in short flights from a perch. Bats adjusted their call frequency to maintain the highest-frequency echoes from background in a forward-directed, spatially limited sector at a constant maximal frequency. This Doppler-shift-compensation strategy guaranteed that echoes of insects flying in front of the bats were received at the sensitive center of their auditory fovea while masking background echoes were received at lower frequencies. Our results reveal an active sensing strategy allowing segregation of signals from background input under natural conditions.